Arterial Flow Regulator Enables Transplantation and Growth of Human Fetal Kidneys in Rats. Issue 6 (22nd January 2015) - Chang, N. K.; Gu, J.; Gu, S.; Osorio, R. W.; Concepcion, W.; Gu, E.
<x xml:space="preserve">Abstract</x> Here we introduce a novel method of transplanting human fetal kidneys into adult rats. To overcome the technical challenges of fetal‐to‐adult organ transplantation, we devised an arterial flow regulator (AFR), consisting of a volume adjustable saline‐filled cuff, which enables low‐pressure human fetal kidneys to be transplanted into high‐pressure adult rat hosts. By incrementally withdrawing saline from the AFR over time, blood flow entering the human fetal kidney was gradually increased until full blood flow was restored 30 days after transplantation. Human fetal kidneys were shown to dramatically increase in size and function. Moreover, rats which had all native renal mass removed 30 days after successful transplantation of the human fetal kidney were shown to have a mean survival time of 122 days compared to 3 days for control rats that underwent bilateral nephrectomy without a prior human fetal kidney transplant. These in vivo human fetal kidney models may serve as powerful platforms for drug testing and discovery.